Neonatal Systemic Thromboembolism Secondary to Ductus Arteriosus Aneurysm and Patent Foramen Ovale. (31st July 2011) - Singh, Jasmeet; Kobayashi, Daisuke; Chen, Michael Y.; Anthony, Evelyn Y.; Williams, Derek A.
ABSTRACT: Ductus arteriosus aneurysm (DAA) can be associated with neonatal thromboembolism. We report a neonate with systemic thromboembolism causing acute cerebral infarction with DAA, arterial, and venous thrombosis, discovered on CT angiography. The role of DAA was suspected as a potential etiology of systemic thromboembolism in this case. CT angiography with three‐dimensional reconstruction was valuable delineating the adjunctive vascular structures. Screening for presence of DAA may be considered in the neonatal thromboembolism.